Analisis Rendahnya Minat Belajar Siswa pada Mata Pelajaran Bahasa Indonesia di Kelas V SDN 3 Cintabodas Kec. Culamega - Sunanih Sunanih; Anita Dewi A; Alya Aditya; Nurul Fadhillah A; Rini Putri R; Ba’dia Akbar W; Yasa Raihan T; Sofa Rahma A; Putri Maspupah; Putri Rahayu P; Adam Firman F; Sherlina Sherlina; Cucu Permata S (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Interest is a sense of interest in something, while learning is the process of producing knowledge, skills and behavior. therefore, interest in learning is an interest in the learning process. This research focuses on the low interest in seeking knowledge by students in Indonesian language learning at level 5 of public elementary school 3 cintabodas, culamega sub-district. This research serves to identify things that make the lack of interest in participating in Indonesian language learning and its influence on the skills of students in capturing and applying to Indonesian language learning. the results of the study indicate that the lack of interest of students in participating in Indonesian language learning is due to the views of students who think that Indonesian language learning is easy and monotonous learning methods in order to develop Indonesian language learning, teachers are advised to apply creative learning methods with varied media. this analysis uses a descriptive qualitative approach with information obtained through question and answer results and evidence and involves educators as the main source.